The Valorising Pitch: How Digital Start‐ups Leverage Intermediary Coverage - Pollock, Neil; Chapple, Duncan; Chen, Suwen; D’Adderrio, Luciana (Journal of Management Studies, 2023)
AbstractAs an unknown quantity, new ventures rely on influential intermediaries to endorse them. However, in some areas, like digital entrepreneurship, there is fierce competition for intermediary attention. Failing to garner intermediary support can mean ventures lack the resources needed to prosper. Still, it is unclear how they attract coverage, how intermediaries evaluate those vying for attention, and what influence this has on venture development. We conducted qualitative inductive research on how digital ventures sought coverage from industry analysts. Our process model of intermediary evaluation shows how ventures must perform a ‘valorising pitch’ to move from being an unknown quantity to engaging the intermediary to being valorised. Drawing on valuation studies scholarship, we propose an enhanced model of intermediary evaluation that depicts industry analysts as not just identifying but also ‘creating’ the value of ventures. We offer contributions to the literature on new venture development, intermediaries and digital entrepreneurship.